Media Advertisement: Does it Really Influence the Purchase Intention? - Mubarak Kaldeen; M. S. Ishar Ali (International Journal on Economics, Finance and Sustainable Development, 2022)
Marketers use a variety of information channels to sway consumer behavior. Every advertisement using different media has a unique mix that engages consumers in a unique way. Consumer media habits have shifted as a result of digitalization. As a result, a better understanding of advertisements on various media platforms and their implications for CB is required. The goal of this study is to check how advertisements affects consumer purchase intentions in the Sri Lankan smart phone market. It reflects how people react to different types of advertisements. The study employed the survey method, with data collected from 250 participants. The data was analyzed using statistical tools such as Cronbach's alpha, correlation, and regression tests. According to the R Square value, media advertisements accounts for 34% increase in purchase intention. Radio commercials, billboard advertisements, and newspaper advertisements, on the other hand, all have a negative impact. The purchase intention of Smart phone is positively influenced by TV, online and social media advertisements. Marketers must use social media to promote their devices. Marketing managers can learn from this study and engage in suitable media to achieve the objectivity of their commercial advertisements.